Makna Amanah dan Akuntabilitas dalam Praktik Keuangan Bank Syariah - Sarah Zettira Agam Darwis; Nur Ikhlasul Amal; Arsal, Muryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Islamic banks operate not only as financial intermediaries but also as institutions rooted in Islamic ethical values. Trust (amanah) and accountability represent core principles guiding financial management in Islamic banking. This study explores the meaning of amanah and accountability and examines how both principles are implemented in Islamic banking practices. Using a qualitative interpretive approach, data were gathered through in-depth interviews, participant observations, and systematic document analysis. The findings indicate that amanah is understood not merely as an individual moral obligation, but as an institutional principle embedded within organizational policies, corporate culture, and governance frameworks. Accountability is reflected through transparent financial reporting, effective internal audit systems, risk management procedures, and the supervisory role of the Sharia Supervisory Board. The integration of amanah and accountability enhances organizational integrity, strengthens stakeholder confidence, and improves decision-making processes. Ultimately, the study demonstrates that embedding these ethical principles contributes to public trust, regulatory compliance, and the long-term sustainability of Islamic banking institutions in increasingly competitive.